(untitled) (Research, Society and Development, 2020)
In Brazil, leprosy represents an important public health problem because it is of great endemicity in the country. The present work aims to characterize the epidemiological characterization of leprosy in the state of Piauí, from 2008 to 2018. The study has a retrospective, descriptive, documentary and quantitative basis. Data were provided by the Piauí State Health Department (SESAPI) and were analyzed taking into account the following parameters: disease operational classification, gender, age and education level. From the data analysis, it was found a considerable prevalence of leprosy in the state of Piauí, and this prevalence may be related to the levels of socioeconomic development of the region. The number of cases of multibacillary leprosy in the state of Piauí, from 2008 to 2018, was a total of 7,523 cases and paucibacillary, with a total of 5,724, and the prevalence detected was higher in men with 53% of cases, while women accounted for 47% of cases. It was found a high prevalence in individuals over 15 years of age, with 11,657 reported cases. There was also a higher occurrence of leprosy cases in individuals who have between the 1st and 4th grade of incomplete elementary school, followed by individuals who have between the 5th and 8th grade of illiterate and illiterate. It is concluded that the predominance of multibacillary classification (MB) may be related to the inadequacy of the diagnostic process in the healthcare network. Regarding gender, it is possible to indicate differences in access in terms of the ability to reach health services.